Solvent extraction of oleo-resins from vanilla (vanilla planifolia andrews) using ultrasonic multipurpose extractor pilot plant system (UMEPPS) - Ahmad Ziad, Sulaiman (2006)
Vanillin (4-hydroxy-3-methoxybenzaldehyde) is an invaluable aroma molecule, useful as food flavouring materials, fragrances, and pharmaceutical or directly in medicine. Vanilla plant (scientifically known as Vanilla planifolia Andrews) is the major sources of natural vanillin produced worldwide. The solvent extraction using ultrasonic multipurpose extractor pilot plant system (UMEPPS) was evaluated as a simpler and more effective alternative to conventional extraction methods for the extraction of oleo-resins from vanilla plant. The vanilla bean samples is extracted with different types of solvent (hereby referred as ethanol and hexane), varies types of vanilla bean surface area (grinded vanilla beans and chopped vanilla beans into 2 cm long) within several limits of time under direct sonication by an ultrasound probe horn located inside the ultrasonic extraction vessel. The mixture of solvent and the solute then undergo the separation process in the evaporation vessel to separate the solute from the solvent. The final separation is done in the thin film evaporator to purify the crude from the last percent of remaining solvent. The enhancement of extraction of oleo-resins from cured vanilla beans by ultrasound attribute to the phenomenon of cavitation produced in the solvent by the passage of an ultrasonic wave. Ethanol appears to be the best extraction solvent with the maximum extraction yield occurs when the grinded vanilla beans is used. 120 minutes seem to be the ideal extraction time for extraction using UMEPPS. The employing of ultrasound to the solvent extraction gives a significant reduction in extraction time and increasing maximum extraction yields. Vanillin was analyzed using HPLC on a Nucleosil C18 column by using water and methanol (40:60) as the mobile phase and retention time was only 2.245 min (extraction using hexane) and 2.107 min (extraction using ethanol) compared to the standard solution which is 2.159 min.